Comparative study of the frozen elephant trunk and classical elephant trunk techniques to supplement total arch replacement for acute type A aortic dissection. (21st April 2019) - Inoue, Yosuke; Matsuda, Hitoshi; Omura, Atsushi; Seike, Yoshimasa; Uehara, Kyokun; Sasaki, Hiroaki; Kobayashi, Junjiro
Abstract: OBJECTIVES: In patients with acute type A aortic dissection, the use of the frozen elephant trunk (FET) procedure with total arch replacement (TAR) has been indicated for emergency operations to obtain thrombosis of the distal false lumen (FL). However, data comparing the FET and the classical elephant trunk (CET) procedures, including the incidences of mortality, morbidity, spinal cord injury and aortic remodelling, have not yet been reported. The goal of this study was to compare the early outcomes of TAR with the FET and the CET procedures. METHODS: The past 7 years of medical records of 323 patients with type A aortic dissection who underwent emergency surgery were reviewed retrospectively, and 148 patients who underwent TAR were shortlisted for the study. First, the patients were divided into 2 groups, the CET group ( n  = 115; age 65 ± 12 years) and FET group ( n  = 33; 67 ± 11 years), to compare the early operative outcomes, including mortality and morbidity. Second, 86 patients (CET 56; FET 30) fulfilling the inclusive criteria (inserted length of elephant trunk ≥5 cm, involvement of dissection at the descending aorta and sufficient computed tomographic evaluation at ≥6 months after the operation) were compared to evaluate the patency and diameter of the FL at each segment of the downstream aorta. RESULTS: The in-hospital mortality rate was 8.1% (12/148), without significant differences between the 2 groups (CET 8.7% vs FET 6.1%; P  = 1). No spinal cord ischaemia was encountered in either group. The incidence of postoperative FL patency at the level of the left lower pulmonary vein was 30% in the FET group, which was significantly lower than that in the preoperative state (73%) and in the CET group (77%). The downsizing of the aortic diameter at the distal edge of the CET or the FET, the left lower pulmonary vein and the coeliac axis was significant in the FET group 6 months after TAR. CONCLUSIONS: According to our initial experience, the FET compared to the CET procedure showed comparable early complications and an advantage concerning FL thrombosis and aortic remodelling at early follow-up examinations.